The Strategic Behavior of Business Leaders with regard to the Daip Professional Integration Assistance Scheme - Case Study: The Wilaya of Bejaia - - KICHER, Idir; FARADJI, Mohamed Akil (Social Sciences Journal)
The concept of the professional insertion is well and more complicated than one might think. It is an over all complex process. It is true that in Algeria, the work market seems to be exclusively governed by the simple ¨offer and demand¨ policy, but it is actually more complex than what one might think. It is a network composed of many actors that are: the state, the business leaders and the young graduated students. Within this network, interactions between the actors occur (embeddedness). Each one try to satisfy his needs and reach his goals by using different and appropriate strategies. In this paper, we will only examine the strategies developed by the business leaders of the different legal sectors (administrative, private economic and public economic) vis-à-vis the DAIP. Is they will play the game to participate in the reduction of the rate of unemployment in general and particularly that of graduated students by creating stable and lasting jobs?